Dual path effects of self-worth on status consumption: evidence from Chinese consumers. Issue 7 (19th December 2019) - Cui, Hongjing; Zhao, Taiyang; Smyczek, Slawomir; Sheng, Yajun; Xu, Ming; Yang, Xiao
Abstract : Purpose: The purpose of this paper is to examine the effect of self-worth on status consumption, focusing on the mediation of self-enhancement and self-compensation and the moderation of power distance belief (PDB) in the relationship of threats to self-worth and consumer choice. Design/methodology/approach: Experiments are used to collect data. Three studies are designed to test the relationship between self-worth, self-enhancement and self-compensation, PDB and status consumption. In total, 180 MBA students participate Study 1, 186 and 244 undergraduate students participate Studies 2 and 3, respectively. ANOVA and bootstrapping method are adopted to analyze the data by using SPSS version 19.0. Study 1 tests the influence of self-worth on status consumption; Study 2 examines the mediation role of self-enhancement and self-compensation; and Study 3 tests the moderation role of PDB. Findings: Results indicate that situational self-worth perception has dual path effects on status consumption. Both improvements in – and threats to – self-worth have a positive impact on status consumption. Improvements in self-worth affect status consumption through the mediation of self-enhancement motives. Threats to self-worth affect status and non-status consumption through the mediation of the self-compensation motive. In the context of a threat to self-worth, compared with consumers with a low PDB, high-PDB consumers have higher purchase intention for status goods but not non-status goods. Research limitations/implications: In this study, improvements in – and threats to – self-worth are momentarily manipulated. The authors present one product in each experiment, but what would happen if both status goods and non-status goods were shown to participants? Which one will the authors choose under different self-worth manipulations? And how long can the effects last? These questions should be answered in future research. Practical implications: This research provides a venue for marketers to introduce and advertise status goods. Marketing practitioners should establish the link between self-worth and status consumption appeals. In the Asia-Pacific markets, Confucian value is important to consumers, and high power distance is important in Confucianism. Thus when developing markets in China, international companies should emphasize Confucian values in the design of advertisements or other promotional items. Further, marketing for status goods should attach importance to the expression of their symbolic meanings. Originality/value: This study contributes to the literature on self-worth and status consumption. It also explores the dual path of the effect of self-worth on status consumption. The motives of self-enhancement and self-compensation are first proposed and tested to explain the mechanism, which differentiates the study from prior work and gives a more reasonable explanation for status and compensatory consumption. The moderation role of PDB delineates the boundary for the effect of a threat to self-worth on status consumption.